2005
DOI: 10.1038/sj.npp.1300696
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Disruption of Neocortical Development Alters Prefrontal Cortical Neuron Responses to Dopamine in Adult Rats

Abstract: A growing body of evidence suggests that structural changes in the cortex may disrupt dopaminergic transmission in circuits involving the prefrontal cortex (PFC) and may contribute to the etiology of schizophrenia. In this study, we utilize a rodent model of neonatal disruption of cortical development using prenatal administration of the mitotoxin methylazoxymethanol acetate (MAM). Using intracellular recordings in vivo, we compare the physiology of prefrontal cortical neurons and their responses to topical ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 85 publications
(78 reference statements)
2
26
1
1
Order By: Relevance
“…Lesions of the prefrontal cortex have been shown to selectively increase perseveration to a previously learned dimension in non-human primates (Dias et al, 1996) and humans (Elliott et al, 1995;Owen et al, 1993). Given the likelihood that MAM disrupts prefrontal cortex function (Flagstad et al, 2004;Lavin et al, 2005) it would be expected that MAM-treated animals would likewise show increases in perseveration, and that this might serve as the basis for the deficit observed in the present study. In addition to an impairment in EDS learning, MAM-treated animals were impaired when required to make a simple reversal of a previously acquired discrimination (for two out of three reversals).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Lesions of the prefrontal cortex have been shown to selectively increase perseveration to a previously learned dimension in non-human primates (Dias et al, 1996) and humans (Elliott et al, 1995;Owen et al, 1993). Given the likelihood that MAM disrupts prefrontal cortex function (Flagstad et al, 2004;Lavin et al, 2005) it would be expected that MAM-treated animals would likewise show increases in perseveration, and that this might serve as the basis for the deficit observed in the present study. In addition to an impairment in EDS learning, MAM-treated animals were impaired when required to make a simple reversal of a previously acquired discrimination (for two out of three reversals).…”
Section: Discussionmentioning
confidence: 57%
“…MAM treatment could have impaired performance on the set-shifting task by altering functioning in one or all of these brain areas. The prefrontal cortex would seem a likely candidate since several previous reports have shown that MAM treatment at gestation day 17 disrupts prefrontal morphology and function (Flagstad et al, 2005;Lavin et al, 2005;Moore et al, 2006). It is unclear as to whether difficulties in shifting attentional set are due to a failure to ignore a previously reinforced dimension or to attend to a previously irrelevant dimension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, although it has been shown that MAM-exposed offspring display dopaminergic dysregulation and cortical impairments consistent with the neurodevelopmental hypothesis of schizophrenia, the administration of an antimitotic compound could also disrupt functioning in many other organs. 217 Despite these shortcomings, such models complement the literature on schizophrenia in humans by providing a more direct assessment of the effects of abnormal neuronal development and cell migration on the development of schizophrenia in a manner that could not be carried out with human participants.…”
Section: Neurogenesis Disruptionmentioning
confidence: 99%
“…As an alternative to genetic approaches, schizophrenia has also been modeled developmentally by administration of a mitotoxin methylazoxymethanol (MAM) on gestational day 17 (GD17) to rats. This model is thought to recapitulate a disruption of developmental process and leads to schizophrenia-like phenotypes in rodent offspring, which include altered neuronal processing (Lavin et al, 2005;Goto and Grace, 2006;Lodge and Grace, 2007). The MAM gestational model of schizophrenia also shows an increase in baseline gamma activity in the prefrontal cortex in awake animals (Kocsis et al, 2013).…”
Section: Animal Models Of Schizophrenia With Relation To Resting Gammmentioning
confidence: 99%